Modelling and Simulation of the Mechanical Response of a Dacron Graft in the Pressurization Test and an End-To-End Anastomosis - Garcia-Herrera, C (Elsevier Ltd, 2016)
This work presents the modeling and simulation of the mechanical response of a Dacron graft in the pressurization test and its clinical application in the analysis of an end-to-end anastomosis. Both problems are studied via an anisotropic constitutive model that was calibrated by means of previously reported uniaxial tensile tests. First, the simulation of the pressurization test allows the validation of the experimental material characterization that included tests carried out for different levels of axial stretching. Then, the analysis of an end-to-end anastomosis under an idealized geometry is proposed. This case consists in evaluating the mechanical performance of the graft together with the stresses and deformations in the neighborhood of the Dacron with the artery. This research contributes important data to understand the functioning of the graft and the possibility of extending the analysis to complex numerical cases like its insertion in the aortic arch. © 2016 Elsevier Ltd.